A comparative study of particle size analysis in fine powder: The effect of a polycomponent particulate system - Choi, Heekyu; Lee, Woong; Kim, Dong-Uk; Kumar, Shalendra; Ha, Jonghak; Kim, Seongsoo; Lee, Jungeun (The Korean journal of chemical engineering, 2009)
We report the particle size distribution of poly component particulate systems studied in three kinds of experimental methods. Six analyzers, such as Mastersizer Microplus (Malvern Instruments Ltd., UK), LS230 (Coulter Electronics Ltd., USA) LMS30 (Seishin, Japan), Analysette22 (Fritsch, Germany), HELOS (Sympatec, Germany) based on a laser diffraction and scattering method, and the SKC-2000S (Seishin Co., Ltd., Japan) based on the centrifugal sedimentation method, were used to study the particle size distribution. The results do not show reasonably good agreement between the different analyzers and different sample systems. There is a discrepancy regarding the absolute values, which can be explained by the fact the techniques used are based on different measuring principles. The results of the present study reflect that the investigator must carefully select the particle size analyzer for a particular application. Therefore, we suggest that it is necessary to measure the particle size distribution by using at least two types of analyzers or more of different makers.